Decreased m6A Modification of CD34/CD276(B7-H3) Leads to Immune Escape in Colon Cancer - Zhou, Yiran; Zhou, Haodong; Shi, Jianlin; Guan, Aoran; Zhu, Yankun; Hou, Zongliu; Li, Ruhong (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have reported that m6a modification promotes tumor immune escape by affecting tumor microenvironment(TME). Due to the complexity of TME, a single biomarker is insufficient to describe the complex biological characteristics of tumor and its microenvironment.Therefore, it is more meaningful to explore a group of effective biomarkers reflecting different characteristics of cancer to evaluate the biological characteristics of solid tumors.Here, the immune gene CD34/CD276 with different m6A peak was obtained by m6A sequencing(MeRIP-seq) of colon cancer (CRC)clinical samples and combined with MsIgDB data, which was used to perform cluster analysis on TCGA-COAD level 3 data.The CD34/CD276 as a molecular marker for CRC prognosis was confirmed by survival analysis and immunohistochemical assay. Further bioinformatics analysis was carried out to analyze the molecular mechanism of CD34/CD276 affecting the TME through m6a-dependent down-regulation and ultimately promoting immune escape of CRC.